ICTs improving family farming - Maru, Ajit; Tafuna'I, Faumuina (Technical Centre for Agricultural and Rural Cooperation, 2014)
ICTs are transforming the lives of family farmers, giving them better access to information, markets, services and inputs, and making them more resilient to external shocks